2019
DOI: 10.1016/j.abrep.2019.100164
|View full text |Cite
|
Sign up to set email alerts
|

Stop smoking practitioner consensus on barriers and facilitators to smoking cessation in pregnancy and how to address these: A modified Delphi survey

Abstract: Introduction Pregnant women can experience barriers and facilitators towards achieving smoking cessation. We sought consensus from smoking cessation practitioners on how influential pre-identified barriers and facilitators can be on pregnant women's smoking behaviour, and how difficult these might be to manage. Suggestions for techniques that could help overcome the barriers or enhance the facilitators were elicited and consensus sought on the appropriateness for their use in practice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…The convenors welcomed the participants and informed them of what the meeting would entail. The participants were asked to read lists of barriers and facilitators (B&Fs) for smoking cessation in pregnancy and techniques that addressed these (derived from previous research [ 23 , 24 ]). These B&Fs and techniques were grouped into Theoretical Domains Framework (TDF) domains prior to the meeting [ 24 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The convenors welcomed the participants and informed them of what the meeting would entail. The participants were asked to read lists of barriers and facilitators (B&Fs) for smoking cessation in pregnancy and techniques that addressed these (derived from previous research [ 23 , 24 ]). These B&Fs and techniques were grouped into Theoretical Domains Framework (TDF) domains prior to the meeting [ 24 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…These interventions can be delivered in a group or on an individual basis, either face to face or over the telephone, with a specialist advisor [ 22 ]. Recent research considered smoking cessation experts’ views on which B&Fs should be addressed as a priority, when supporting pregnant women in their quit attempts [ 23 , 24 ]. In these studies, the experts identified smoking being a norm in women’s social circles and a lack of support from partners to be the key barriers to successfully quitting whilst pregnant.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations